Parâmetros físico-químicos da água e bioacumulação de metais em peixes de tanques-rede em Entre Rios do Oeste-PR - Weiss, Luciane Aline (2017)
The present study aimed to monitor the physicochemical variables of water and bioaccumulation of biologically essential metals, copper (Cu), iron (Fe), zinc (Zn), and manganese (Mn), and toxic heavy metals, cadmium (Cd), chromium (Cr) and lead (Pb) in skin, gills, fillet and liver of Nile tilapia (Oreochromis niloticus) grown in net tanks. The work was carried out from October 2015 to September 2016, in the basin of the river São Francisco Verdadeiro in Entre Rios do Oeste. For water quality monitoring, three sites were delimited and georeferenced in the longitudinal axis of the tilapia farming downstream, at the point of reference of the net tanks and upstream of the aquaculture area. In the evaluation of the effects of water column vertical dynamics, three depths were used: epilimnium, metalimnium and hypolimnium. The physical-chemical variables temperature, transparency, dissolved oxygen, pH, conductivity, total solids and water turbidity were monitored. Monthly 10 specimens of Nile tilapia were collected for evaluation of metals bioaccumulation. The total metals contents were measured after nitro-perchloric digestion of the samples and read by atomic absorption spectrometry, UV-VIS flame modality. The mean values of the physical-chemical variables of water and metals in the different organs of tilapia were grouped by season of the year and submitted to analysis of variance (ANOVA) and in case of significance the means were compared by Tukey test at 5 % probability. The monthly bioaccumulation values in the evaluated organs were submitted to GENES computational application for the principal components analysis. The three sites in the longitudinal axis of tilapia farming influenced the average values of dissolved oxygen in the water (P<0.05). The temperature and pH of the water presented decreasing values (P<0.05) in relation to depth, while the mean value of dissolved oxygen in the epilimium was higher (P<0.05) than those observed in metalimetry and hypolimnion. Regarding the bioaccumulation of metals in the fish, there was a seasonal effect, independent of the organs analyzed, for copper and zinc concentrations. Samples of gills, skin and liver of Nile tilapia presented concentrations of Pb above that allowed by legislation. The values of chromium in all samples have been above the limits stipulated by the legislation. Cadmium was found in excessive concentrations for skin and gills only in winter. The dispersion of the main components for the metal content in the gills, liver, fillet and skin explain at least 70% of the total variance by the first main components, thus guaranteeing the efficiency of the representation of characteristics studied in the main components used in the graphic analysis. The water quality variables analyzed in tilapia farming meet the standards of Nile tilapia cultivation in the net tank system. Principal components analysis can be used to characterize the bioaccumulation of metallic elements in the gills, liver, fillet and skin of Nile tilapia and their characterization during a year of monthly sampling in tilapicultura in net tanks of the aquaculture area of Itaipu Binacional. Nile tilapia can be considered a potential bioindicator of metals accumulation.